Evaluating Multivariate Normality In Medical Datasets: A Case Study With R - Wan Muhamad Amir W Ahmad; Mohamad Nasarudin Adnan; Farah Muna Mohamad Ghazali; Nor Azlida Aleng; Mohamad Shafiq Mohd Ibrahim; Nurfadhlina Abdul Halim (Research Trends (P) LTD., 2025)
Indexed